Study of histomorphological spectrum of lesions in nephrectomy specimen in a tertiary care hospital in South Gujarat - Bajaj, Himani; Hathila, Rasik (International Journal of Research in Medical Sciences, 2020)
Background: Nephrectomy is a standard surgical procedure in urology indicated in patients with organ confined renal malignancies and irreversible kidney damage resulting from chronic infection, trauma, obstruction and congenital malformation. This study aims to study the histomorphological features of lesions in nephrectomy specimens in a tertiary care hospital, to analyse the neoplastic and non-neoplastic lesions of kidney according to age, gender and site and observe any variation from the conventional pattern. Methods: The present study was conducted in department of pathology, Tertiary care hospital over a period of 5 years and 7 months (1 Jan 2013 to July 31, 2018). This included 4 years retrospective and 1 year 7 months prospective. A total of 73 cases of were studied. Results: Males constituted 65.73% and females constituted 35.27% of all nephrectomy cases. Right kidney was more commonly affected. Highest percentage of patients belonged to 41-50 years age group. 45 cases were of non-neoplastic lesions and 28 cases were of neoplastic lesions. Among neoplastic lesions, one case was benign while remaining 27 cases were malignant. Chronic Pyelonephritis was the most common indication overall and also amongst non-neoplastic lesions with stone identified in 55% cases. Most common neoplastic lesion in nephrectomy specimen was Renal Cell carcinoma (71.4.1%) followed by Wilms tumour (14%). Conclusions: This study gives a fair insight of the current state of incidence of neoplastic and non-neoplastic lesions of kidney requiring surgical intervention.